2016
DOI: 10.5455/jice.20160320022623
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficiency of the Sudanese Roselle (Hibiscus sabdariffa L.), a famous beverage from Sudanese folk medicine

Abstract: Background:Hibiscus sabdariffa L. is a plant native to tropical Africa and intensively cultivated in Sudan. Its calyces are widely consumed with many uses in Sudanese folk medicine.Materials and Methods:The dried calyces of H. sabdariffa were subjected to soak in 80% v/v methanol to get the methanolic extract, which was tested against five Gram-negative and three Gram-positive referenced bacterial strains using disc diffusion method. Selected bioactive phytochemical compounds were also investigated using quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
2
17
0
6
Order By: Relevance
“…[10,12] A plethora of studies revealed the presence of flavonoids, phenolic acids, lignans, triterpenoids and sterols in such family. [10,[17][18][19][20][21][22][23] For instance, Zaki and co-workers [23] applied multiplesolvents extraction to the aerial parts of Z. aegyptium A. Hosny sp. nov.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,12] A plethora of studies revealed the presence of flavonoids, phenolic acids, lignans, triterpenoids and sterols in such family. [10,[17][18][19][20][21][22][23] For instance, Zaki and co-workers [23] applied multiplesolvents extraction to the aerial parts of Z. aegyptium A. Hosny sp. nov.…”
Section: Introductionmentioning
confidence: 99%
“…[25] It is distributed in North Africa and known in the Arab region as (Garmal and Hureim). [17] It was found that it belongs to genus Tetraena, a sister to genus Zygophyllum and recently reassigned to such genus and could be referred as Tetraena simplex (L.) Beier & Thulin (syn. Z. simplex L.) (Zygophyllaceae).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of H. sabdariffa has been reported against foodborne and food spoilage microorganisms, like E. coli O157:H7, is a major foodborne pathogen [23,37], also against Gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumonia, Proteus vulgaris, Salmonella enterica and some multidrug resistant Salmonella strains, in addition to some Gram-positive bacteria such as Bacillus subtilis, S. aureus, Staphylococcus epidermis, and Staphylococcus cereus [24,25,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Finely powdered and extracted in a Soxhlet with 2 L of methanol for 48 h. The methanol was evaporated by vacuum pressure, the ×10 concentrated extract 10 mg/ml was used in further experiments [23,25,31].…”
Section: Plant Materials and Extractionmentioning
confidence: 99%
See 1 more Smart Citation